Administration of Antiarrhythmic Drugs to Maintain Sinus Rhythm After Catheter Ablation for Atrial Fibrillation: A Meta‐Analysis. Issue 4 (7th July 2015) - Xu, Xiuli; Alida, Choumi T.; Yu, Bo
Summary Background Whether the short‐term administration of antiarrhythmic drugs (AADs) to maintain sinus rhythm following catheter ablation (CA) for atrial fibrillation (AF) can prevent the recurrence of AF is still a matter of debate. We searched the PubMed database and the Cochrane Library, and compiled a list of retrieved articles. We included only randomised controlled trials(RCTs) that compared any AADs against control (placebo or no treatment) or other AADs following CA for AF. Statistical analysis of the odds ratio (OR) and corresponding 95% confidence interval (CI) were used to determine the overall effect of both outcomes. The Mantel–Haenszel method was used to pool data of the outcomes of AF recurrence into fixed effect model meta‐analyses. Aims We performed a systematic review to determine the effectiveness of short‐term treatment with AADs on the recurrence of AF after CA. Results Six RCTs were included in this study, with a total of 814 patients. Post‐procedural temporary administration of AADs in patients after CA for AF reduced the early recurrence of AF (antiarrhythmic drug 103 patients [25.3%], control 162 patients [39.8%]; OR 0.47 [95% CI 0.34–0.64]; χ2 = 3.77; P = 0.58; I2 = 0%). No significant difference in patients after CA for AF in the late recurrence of AF (antiarrhythmic drug 148 patients [36.5%], control 171 patients [42.5%]; OR 0.77 [95% CI 0.57–1.03]; χ2 = 3.15; P = 0.68; I2 = 0%). The heterogeneity was zero in both analyses. Conclusion Although the continued administration of AADs after CA for AF can decrease early atrial tachycardias (ATa), this treatment does not prevent late ATa.